Unicorn Diaries : The Goblin Princess - Book 4 - Elliott, Rebecca (New York, New York, 2020)
Greta the goblin princess is bored, but when unicorns Bo and Sunny try to cheer her up by using their powers to make her queen (for a day), they discover just how much trouble a bored--and spoiled--goblin princess can cause for everyone around her.
Keywords: Fiction; Responsibility; Fiction; Princesses; Fiction; Magic; Fiction; Goblins; Fiction; Unicorns; Princesses; Responsibility; Juvenile fiction; Juvenile fiction; Magic; Juvenile fiction; Goblins; Juvenile fiction; Unicorns; Juvenile fiction; Juvenile fiction